Madly, deeply : the diaries of Alan Rickman - Rickman, Alan (Henry Holt and Company, 2022)
Told through his diaries--a twenty-five-year passion project--the beloved actor, political activist, and more grants us access to his thoughts and insights on theater performances, the craft of acting, politics, friendships, work projects, and his general musings on life.